Adapting meaning-centered psychotherapy for World Trade Center responders. Issue 6 (December 2020) - Masterson-Duva, Melissa; Haugen, Peter; Werth, Aditi; Foster, Alyce; Chassman, Emily; Roberts, Kailey; DePierro, Jonathan; Morales-Miller, Massielle; Lowe, Sandra; Pessin, Hayley; Lichtenthal, Wendy; Breitbart, William
Abstract: Objective: To date, nearly 10, 000 World Trade Center (WTC) responders have been diagnosed with at least one type of WTC-related cancer, and over 70 types of cancer have been related to WTC occupational exposure. Due to the observed latency period for malignancies, the WTC Health Program anticipates increases in rates of new cancer diagnoses. Given the growing number of cancer diagnoses in this population, there is an urgent need to develop a novel intervention to address the psychosocial needs of WTC responders with cancer. Meaning-centered psychotherapy (MCP) is a structured psychotherapeutic intervention originally developed to help patients with advanced cancer find and sustain meaning in life despite illness-related limitations. Existential distress and loss of meaning are critical and understudied elements of psychological health that have been widely overlooked among WTC responders with cancer. Method: We have adapted MCP for WTC responders (MCP-WTC) for the treatment of WTC responders who have been diagnosed with WTC-certified cancers. MCP-WTC aims to target the complex crisis in meaning faced by those responders who responded to the 9/11 attacks and subsequently were diagnosed with cancer as a result of their service. Results: We describe the adaptation of MCP-WTC and the application of this intervention to meet the unique needs of those exposed to the terrorist attacks of September 11, 2001 (9/11), participated in the rescue, recovery, and clean-up effort at Ground Zero, and were diagnosed with WTC-related cancer. We highlight the novel aspects of this intervention which have been designed to facilitate meaning-making in the context of the patient's response to 9/11 and subsequent diagnosis of cancer. Significance of results: This work provides a rationale for MCP-WTC and the potential for this intervention to improve the quality of life of WTC responders and help these patients navigate life after 9/11 and cancer.